Barriers and facilitators of loaded self-managed exercises and physical activity in people with patellofemoral pain: understanding the feasibility of delivering a multicentred randomised controlled trial, a UK qualitative study - Michael Skovdal Rathleff; Phillipa Logan; Marcus Bateman; Benjamin E Smith; Fiona Moffatt; Paul Hendrick; James Selfe; Toby O Smith (BMJ Open)
Objectives There is an emergent body of evidence supporting exercise therapy and physical activity in the management of musculoskeletal pain. The purpose of this study was to explore potential barriers and facilitators with patients and physiotherapists with patellofemoral pain involved in a feasibility randomised controlled trial (RCT) study. The trial investigated a loaded self-managed exercise intervention, which included education and advice on physical activity versus usual physiotherapy as the control.Design Qualitative study, embedded within a mixed-methods design, using semi-structured interviews.Setting A UK National Health Service physiotherapy clinic in a large teaching hospital.Participants Purposively sampled 20 participants within a feasibility RCT study; 10 patients with a diagnosis of patellofemoral pain, aged between 18 and 40 years, and 10 physiotherapists delivering the interventions.Results In respect to barriers and facilitators, the five overlapping themes that emerged from the data were: (1) locus of control; (2) belief and attitude to pain; (3) treatment expectations and preference; (4) participants’ engagement with the loaded self-managed exercises and (5) physiotherapists’ clinical development. Locus of control was one overarching theme that was evident throughout. Contrary to popular concerns relating to painful exercises, all participants in the intervention group reported positive engagement. Both physiotherapists and patients, in the intervention group, viewed the single exercise approach in a positive manner. Participants within the intervention group described narratives demonstrating self-efficacy, with greater internal locus of control compared with those who received usual physiotherapy, particularly in relation to physical activity.Conclusions Implementation, delivery and evaluation of the intervention in clinical settings may be challenging, but feasible with the appropriate training for physiotherapists. Participants’ improvements in pain and function may have been mediated, in some part, by greater self-efficacy and locus of control.Trial registration number ISRCTN35272486; Pre-results.